Modernidad clásica - Pahissa-Sáenz (2003)
Casa en Olivos Golf Club en Malvinas Argentinas, prov.Bs.As., año 2001
Keywords: PAHISSA, KARINA; SÁENZ, JAVIER; ARGENTINA; BUENOS AIRES; OLIVOS; COUNTRY CLUBS; VIVIENDAS RESIDENCIALES